A Conversation Analysis of Turn Taking in the Pakistani Classrooms - Iqbal, Mohammad Aamir; Chaudhary, Dr. Naveed Ahmed; Hussain, Zahoor (International Journal of Psychosocial Rehabilitation, 2020)
This study focuses one of the research areas called turn-taking during the conversation in an institutional setting. Conversation is highly dependent on the ways how people take turns during their ordinary talks or the conversation in an institutional setting. The researchers collected data from student’s tests, video- taped classroom interactions and the interviews with the teachers. The researchers adopted a Conversation Analytic [CA] framework in order to analyze how turn- taking was done by the students and teachers in a classroom interaction. The general design of study included the four phases typical of CA research projects: recordings of natural interaction, transcription of the recordings, analysis of selected episodes, and reporting of the research. The instructors of English, both female, and male participated in the study. Much of the classroom interaction was based on the instructors’ talk: to review covered material, to introduce new material, and to evaluate student turns. The analysis of turn-taking in a Pakistani classroom showed that the underlying rules or guidelines of interaction were the same as those found in studies of other languages: one speaker at a time, no gaps, no overlaps. Discipline played an obvious role in this kind of language-teaching methodology. It was also observed that when an instructor did not have control of the class and therefore of the turn-taking system, there were more instances of ‘broken rules’ e.g. more overlaps and more repairs as a result of behavioural lapses.